Testing the Rossby Paradigm: Weakened Magnetic Braking in Early K-type Stars - Travis S. Metcalfe; Pascal Petit; Jennifer L. van Saders; Thomas R. Ayres; Derek Buzasi; Oleg Kochukhov; Keivan G. Stassun; Marc H. Pinsonneault; Ilya V. Ilyin; Klaus G. Strassmeier; Adam J. Finley; Rafael A. García; et al. (The Astrophysical Journal)
There is an intricate relationship between the organization of large-scale magnetic fields by a stellar dynamo and the rate of angular momentum loss due to magnetized stellar winds. An essential ingredient for the operation of a large-scale dynamo is the Coriolis force, which imprints organizing flows on the global convective patterns and inhibits the complete cancellation of bipolar magnetic regions. Consequently, it is natural to expect a rotational threshold for large-scale dynamo action and for the efficient angular momentum loss that it mediates through magnetic braking. Here we present new observational constraints on magnetic braking for an evolutionary sequence of six early K-type stars. To determine the wind braking torque for each of our targets, we combine spectropolarimetric constraints on the large-scale magnetic field, Ly α or X-ray constraints on the mass-loss rate, as well as uniform estimates of the stellar rotation period, mass, and radius. As identified previously from similar observations of hotter stars, we find that the wind braking torque decreases abruptly by more than an order of magnitude at a critical value of the stellar Rossby number. Given that all of the stars in our sample exhibit clear activity cycles, we suggest that weakened magnetic braking may coincide with the operation of a subcritical stellar dynamo.